Impact of mild to severe hemophilia on engagement in recreational activities by US men, women, and children with hemophilia B: The Bridging Hemophilia B Experiences, Results and Opportunities into Solutions (B‐HERO‐S) study. (April 2017) - Baumann, Kimberly; Hernandez, Grace; Witkop, Michelle; Peltier, Skye; Dunn, Spencer; Cutter, Susan; Frick, Neil; Haugstad, Kimberly; Guelcher, Christine; Frey, Mary Jane; Rotellini, Dawn; Clark, David B.; et al.
Abstract: The psychosocial impact of hemophilia on activities was recently investigated in the Hemophilia Experiences, Results and Opportunities (HERO) study (675 people with hemophilia and 561 caregivers of children with hemophilia in 10 countries). The impact of hemophilia B may not be accurately reflected in the HERO results, as ~75% of respondents described issues affecting males with hemophilia A. To address the needs of this population, the Bridging Hemophilia B Experiences, Results and Opportunities Into Solutions (B‐HERO‐S) was developed as a pilot study in the United States in collaboration with the hemophilia community. The analysis reported here assessed engagement in recreational activities and changes to treatment regimens around activities as reported by 299 adults with hemophilia B and 150 caregivers of children with hemophilia B. Nearly all adults with hemophilia B (98%) experienced a negative impact on their participation in recreational activities due to hemophilia‐related issues, and most caregivers (90%) reported that hemophilia B had a negative impact on their child's engagement in recreational activities. One of the main reasons identified for discontinuing past activities was the risk of bruising or bleeding (adults/children with hemophilia B, 49%/41%). In particular, adults with hemophilia B reported a history of activity‐related bleeding, and most adults decreased their participation in high‐risk activities as they aged. Substantial percentages of adults and children with hemophilia B (including mild/moderate severity) altered their treatment regimens to accommodate planned activities. These findings may help inform guidelines for individualizing treatment regimens around participation in recreational activities based on hemophilia severity, baseline factor level, and activity risk and intensity.